Role of Cystatin C in predicting acute kidney injury after surgery - Mustapha, Muhammad Ikhwan; Othman, Ahmad Faidzal; Mat Nor, Mohd Basri; Md Ralib, Azrina; Ab Rahman, Jamalludin; Elagili, Faisal (2022)
Introduction Surgery is a known risk factor for acute kidney injury (AKI) which causes considerable implications on mortality and morbidity. We investigated the incidence of AKI following surgery and determine the diagnostic capability of Cystatin C (CysC) in diagnosing and predicting AKI.